Randomised control trial to compare the efficacy of traditional Thai massage and ultrasound therapy for treating plantar heel pain - Supamas Somphai; Wiraphong Sucharit; Punnee Peungsuwan; Neil Roberts; Uraiwan Chatchawan (BMC Complementary Medicine and Therapies)
Abstract Background Massage is suggested to be an effective treatment for chronic plantar heel pain (PHP). There is, however, no scientific evidence to support this claim. In the present study Traditional Thai Massage (TTM) has been compared with Ultrasound therapy (US) for treating PHP. Methods Sixty PHP patients with a Myofascial Trigger Point (MTrP) present in the calf were randomly assigned to receive a 40-minute single treatment of either US or TTM. Pain Intensity (VAS), Pressure Pain Threshold (PPT), Ankle Dorsiflexion Range of Motion (DROM), and Foot Skin Temperature (FST), were measured before, immediately after, and 24 h after treatment. Results Compared to baseline, both groups showed a significant reduction in pain intensity immediately (CVAS) and 24 h after treatment (MVAS24) (p < 0.01), as well as a significant increase in PPT of the heel immediately after treatment (p < 0.05). However, only the US treatment group showed an increase in PPT in the calf immediately after treatment (p < 0.05). Furthermore, only the US group showed a significant increase in DROM immediately and 24 h after treatment (p < 0.001). The reduction in CVAS and increase in DROM immediately (p < 0.05) and 24 h after treatment (p < 0.01) were significantly greater in the US than the TTM group. Conclusions The significant efficacy of US with stretching for providing pain relief in the treatment of PHP is confirmed. For the first time, TTM has also been demonstrated to be effective in providing pain relief for patients with PHP and may have a potentially useful complementary role, in treating PHP. Trial registration TCTR20210909001 (First Submitted Date: September 2021).